Disproportionately high failure to rescue rates after resection for colorectal cancer in the geriatric patient population: a nationwide study - Diers, Johannes; Baum, Philip; Lehmann, Kai; Uttinger, Konstatin; Baumann, Nikolas; Pietryga, Sebastian; Hankir, Mohammed; Matthes, Niels; Lock, Johann F.; Germer, Christoph-Thomas; Wiegering, Armin (Cancer medicine, 2022)
Background Colorectal cancer incidence increases with patient age. The aim of this study was to assess, at the nationwide level, in-hospital mortality, and failure to rescue in geriatric patients (≥ 80 years old) with colorectal cancer arising from postoperative complications. Methods All patients receiving surgery for colorectal cancer in Germany between 2012 and 2018 were identified in a nationwide database. Association between age and in-hospital mortality following surgery and failure to rescue, defined as death after complication, were determined in univariate and multivariate analyses. Results Three lakh twenty-eight thousands two hundred and ninety patients with colorectal cancer were included of whom 77,287 were 80 years or older. With increasing age, a significant relative increase in right hemicolectomy was observed. In general, these patients had more comorbid conditions and higher frailty. In-hospital mortality following colorectal cancer surgery was 4.9% but geriatric patients displayed a significantly higher postoperative in-hospital mortality of 10.6%. The overall postoperative complication rate as well as failure to rescue increased with age. In contrast, surgical site infection (SSI) and anastomotic leakage (AL) did not increase in geriatric patients, whereas the associated mortality increased disproportionately (13.3% for SSI and 29.9% mortality for patients with AI, both p < 0.001). Logistic regression analysis adjusting for confounders showed that geriatric patients had almost five-times higher odds for death after surgery than the baseline age group below 60 (OR 4.86; 95%CI [4.45-5.53], p < 0.001). Conclusion Geriatric patients have higher mortality after colorectal cancer surgery. This may be partly due to higher frailty and disproportionately higher rates of failure to rescue arising from postoperative complications.